Catalytic synthesis of chiral sulfinimidate esters via oxidative esterification of sulfenamides - Hua-Jie Jiang; Xue-Qin Tu; Xin-Yi Kong; Ju-Yan Wang; Yu-Yang Liu; Meng-Lan Shen; Chuan-Zhi Yao; Qiankun Li; Jie Yu (Nature Communications)
Abstract Aza-sulfur compounds, such as sulfilimines, sulfoximines, etc, are increasingly recognized as essential contributors to advancements in drug development and asymmetric synthesis. Among them, the catalytic enantioselective synthesis of sulfinimidate esters remains an uncharted and formidable challenge. Herein, we unveil an efficient enantioselective oxidative esterification of sulfenamides via chiral sulfinimidoyl iodide intermediates. Using stereogenic-at-Co(III) complexes as catalysts, this approach enables the synthesis of an extensive array of enantioenriched sulfinimidate esters (>70 examples, up to 98.5:1.5 er), offering a versatile platform for the preparation of structurally diverse aza-sulfur compounds.